PROFILE OF PATIENTS WITH KIDNEY DISEASE IN MAKING ONLINE HEMODIALYSIS FOUNDATION PRO-RIM, BALNEÁRIO CAMBORIÚ UNIT - SANTA CATARINA (Fiep Bulletin - online, 2013)
Chronic kidney disease (CKD) has been characterized as a major public health problem, with the consequences, slow progressive and irreversible loss of kidney function, and presenting complex changes in the cardiovascular, nervous, musculoskeletal, immune, endocrine-metabolic and respiratory. The aim of this study was to investigate the socio-cultural context of patients with renal disease on hemodialysis who perform pro-kidney foundation, Unit Balneario Camboriu - Santa catarina.O study was a descriptive and quantitative. We analyzed 26 individuals from June to July 2011 in a Renal Unit. For data collection instruments used were the evaluation form and a questionnaire socio cultural. Conclusion: It was found through the analysis performed, predominantly male, mean age 50, normal weight, not smoking, having high blood pressure (HBP) and associated disease most commonly found, followed by DM, with no history familiar to kidney disease. Through the study concluded that compared to national risk factors, this population is consistent with national data. Aiming to prevent CKD and reduce the impacts caused by treatment measures are needed to promote health and multidisciplinary care, promoting a better quality of life for patients with CKD.
Keywords: chronic renal failure; hemodialysis; epidemiological profile.